Credit Risk and Market Risk on Stock Prices: Study on the Banking Sector Listed on the IDX in 2019-2021 - Alifa, Muthia Nur; Mediawati, Elis (Journal of Business Management and Economic Development, 2024)
This study aims to determine effect of credit risk and market risk on stock price. This research was conducted on bank sector listed on Indonesia Stock Exchange in 2019-2021. The research method used is descriptive and verification with a quantitative approach. The sampling method is purposive sampling method, obtained 37 companies with 111 observations. The data analysis technique used in this research is panel data regression analysis with E-Views 12 software. The results of this study show that either partially or simultaneosly credit risk and market risk has a significant effect on stock prices.